The Promise of Early Childhood Development in Latin America and the Caribbean - Vegas, Emiliana; Santibáñez, Lucrecia (Washington, DC: World Bank, 2012)
This book aims to fill gaps in existing knowledge about early childhood development (ECD) efforts in Latin America and the Caribbean by reviewing a selection of ECD programs in the region, including those in early childhood education, health, and nutrition, and distilling lessons related to their design, implementation, and institutionalization. The book surveys existing evidence on the impact of programs worldwide that provide support to children during the period before birth through age six, including programs in developed and developing nations. It presents a compelling evidence-based argument for greater investment in ECD programs in Latin America and the Caribbean, while highlighting the need for both more rigorous evaluations and more accurate cost accounting of such programs. Improved evaluations and cost tracking will generate better data on how to effectively design, fund, and provide quality ECD programs to all children in the region, especially those from low-income families.